ANALISIS KESALAHAN MAHASISWA DALAM MENYELESAIKAN SOAL KALKULUS DIFERENSIAL BERDASARKAN KRITERIA WATSON - Andi Karlina (STKIP Paris Barantai, 2019)
This type of research used in this research is descriptive qualitative research. This study aims to describe what errors were made by STKIP Paris BarantaiKotabaru mathematics students in solving differential calculus problems based on Watson's criteria, as well as what factors caused errors made by students. The results obtained are as follows; students with a high level of ability (MT) based on Watson's criteria in solving differential calculus problems is an incorrect procedure. while the mistakes made by students with high levels of ability (MT) based on Watson's criteria in solving differential calculus problems are conflict level responses. The factors that cause errors made by students with a high level of ability (MT) in solving differential calculus problems based on Watson's criteria are inaccurate in conducting simplification operations on fractions and making mistakes in manipulating algebra. While the factors that cause mistakes made by students with low levels of ability (MR) are not understanding the form of problems so that solving problems but not in a logical way. Keywords: Error analysis, Differential Calculus, Watson Criteria